2009
DOI: 10.1007/s12011-009-8384-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidant System in the Tumor and in the Blood of Patients with Nasopharyngeal Carcinoma

Abstract: Reactive oxygen species play a key role in cancer development by inducing and maintaining the oncogenic phenotypes of cancer cells. In this study, we examined lipid peroxidation and antioxidant enzymes activities in the blood and in the tumor of nasopharyngeal carcinoma patients. Plasma malondialdehyde, conjugated dienes, erythrocytes catalase, and superoxide dismutase activities have been measured in 30 untreated nasopharyngeal carcinoma patients and 30 controls on one hand. On the other hand, tumor malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…[29][30][31][32] Our study found a reduction of erythrocyte membranes micro viscosity in protein-lipid regions (τ CII ) in cancer patients, which is consistent with data of authors who have reported analogous structural changes in cell membranes in patients with other cancer diseases. [33,34] The correlation of AO enzymatic activity and MDA level in erythrocytes was obtained with the stage of lung cancer of patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[29][30][31][32] Our study found a reduction of erythrocyte membranes micro viscosity in protein-lipid regions (τ CII ) in cancer patients, which is consistent with data of authors who have reported analogous structural changes in cell membranes in patients with other cancer diseases. [33,34] The correlation of AO enzymatic activity and MDA level in erythrocytes was obtained with the stage of lung cancer of patients.…”
Section: Discussionsupporting
confidence: 89%
“…[1] Extensive epidemiological [26] and statistical date [27] clearly establish role of cigarette smoking in the genesis of lung cancer and head and neck cancer. It is known that neoplastic transformation is accompanied by changes in AO status, [28] in the extent of lipid oxidation, [29][30][31][32] micro viscosity of membranes and lipid composition [33,34] and an increase of DNA breaks number in both tumor tissue and leukocytes of blood. [35][36][37][38][39] The changes in these parameters indicate the involvement of oxidative stress in the process of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Burlakova et al noted that the absence of a response these enzymes indicate a weakening of antioxidant enzymes system [118]. They found no change in the malondialdehyde (MDA) level, which is consistent with the previous work in patients with oral cancer [117,145,146,147]. In initial period its level is increased, but later it decreased [118].…”
Section: Enzymatic Antioxidantssupporting
confidence: 72%
“…These types of mutation are reported in genes whose dysfunction is involved in the genesis of cancer [6] . ROS may also play a key role in cancer development by inducing and maintaining the oncogenic phenotypes of cancers [7] . The highly significant correlation between consumption of fats and oils and death rates from leukemia and malignant neoplasia of the breast, ovaries and rectum among persons over 55 years may be a reflection of greater lipid peroxidation [8] .…”
Section: Oxidative Damage To Dna and Cancermentioning
confidence: 99%